The Influence of As-Sa'ah Media on Improving Students' Understanding of 'Adad Tartibi in Grade VIII at MTs Ishlahul Amanah - Devia, Rahma; Nursyamsiah, Nunung; Khalid, Shofa Musthofa (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The current development of Arabic language learning in Indonesia is still not optimal, because there are still many obstacles that have to faced especially by students in its implementation. The study examines the impact of "As-Sa’ah Media" on enhancing students' comprehension of 'adad tartibi (ordinal numbers) in Arabic language learning in Indonesia. The research employs a Quasi-Experimental design, specifically the Nonequivalent Pretest-Posttest Control Design. The population in this study was taken from grade VIII students of MTs Ishlahul Amanah totaling 215 students, involving two classes as a research sample. Class VIII F, with students facing difficulties in 'adad tartibi, serves as the experimental group, while Class VIII E, demonstrating better understanding, serves as the control group. Pretest and posttest assessments on As-Sa'ah material are administered, with hypothesis testing conducted using one sample t-test. Results indicate that students using As-Sa’ah media show improved comprehension of 'adad tartibi, evidenced by increased average grades compared to those using conventional methods.